Research and Realization of Interpolation for Real-time TV Picture Motion Detection - 李舒; 张家谋 (Tongxin xuebao)
A new method of interpolation for TV signal based on realtime motion detection are proposed and analysized by 2D spectrurn. This paper goes on to use this new method to realize progressive scanning or doubling scanning so that good picture quality can be achieved. It emphasizes on adaptive interpolation and uses hardware to perform the method. The method discussed in this paper gets good visual effect.